2020
DOI: 10.1038/s41598-020-60565-7
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus compromises the survival of diffuse large B-cell lymphoma patients treated with (R)-CHOP – the PLRG report

Abstract: Comorbidities impair the prognosis of diffuse large B-cell lymphoma (DLBCL). Type 2 diabetes mellitus (DMT2) increases the risk of other comorbidities, e.g., heart failure (HF). Thus, we hypothesized that pre-existing DMT2 may negatively affect the outcome of DLBCL. To verify this, DLBCL patients treated with (R)-CHOP were enrolled. 469 patients were eligible, with a median age of 57 years; 356 patients had advanced-stage DLBCL. 126 patients had high-intermediate and 83 high-risk international prognostic index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…12 In an analysis by the Polish Lymphoma Research Group of 469 DLBCL patients treated with CHOP or R-CHOP, diabetic patients had a 15% lower 5-year OS. 13 It has been hypothesized…”
Section: Discussionmentioning
confidence: 99%
“…12 In an analysis by the Polish Lymphoma Research Group of 469 DLBCL patients treated with CHOP or R-CHOP, diabetic patients had a 15% lower 5-year OS. 13 It has been hypothesized…”
Section: Discussionmentioning
confidence: 99%
“…The four selected risk features have also consistently been found to be independently associated with reduced OS in DLBCL. [22][23][24][25] Although further research is certainly warranted, these reports further underpin the predictor selection proposed in this analysis.…”
Section: Discussionmentioning
confidence: 79%
“…Other recently reported studies have shown that a diagnosis of type 2 diabetes is associated with worse outcomes in the context of DLBCL [ 46 , 47 ]; however, sex-specific differences have not been previously reported. In this study, a diagnosis of diabetes had a significant negative impact on male OS ( p = 0.004).…”
Section: Discussionmentioning
confidence: 97%